Annual Plan 1993-94 Volume-IX Hill Areas Government of Assam - Planning Commission (Planning Commission, 1993)
While preparing the draft 8th Five year Plan as well as the Annual Plan 93-94, guidelines of the Planning Commission have been followed and exphasos has been given to maximise the benefits on roads from existing capacity rather than increasing the reed lengths under New schemes as like previous years and hence, the proposed increase of road length after a five year plan period is shown to be 637.00 KM only which seems to be very low in comparison to the increase of road lengths during previous five year Plan.
Government of Assam, Development Commissioner for Hill Areas